Prevalence and Predictors of Irritable Bowel Syndrome among Medical Students - Farah, Randa; Khamis, Nadia; Abu Sneineh, Awni; Khatib, Aseil; Haddadin, Sophia; Darwish, Mohammad; Rayyan, Yaser (Jordan Medical Journal, 2022)
Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal disorders, and medical students are at a higher risk for this disorder, given their stressful lives. This study aims to identify the prevalence of IBS and the associated risk factors among MS. A cross-sectional study was conducted among medical students at all academic levels. Data were collected from January to September 2018 using a validated, self-administered, and anonymous questionnaire. Five hundred eighty-five students were included, and an IBS diagnosis was made in 37 students. Older students and those in higher clinical years are at greater risk for developing IBS (P <.02 and.001, respectively). The factors associated with IBS (adjusting for known confounders) included a family history of IBS [adjusted odds ratio (AOR): 7.06 (95% CI: 2.923 - 17.069)], rare use of over-the-counter pain medications, [AOR: 2.806; 95% CI: 0.004-0.431; P <.003] and students experiencing high levels of anxiety [AOR : 3.33 (95% CI: 1.392 -7.981); P<.002]. In this study, the risk of IBS among medical students was 6.6%.